Mutation detection in FGFR2 craniosynostosis syndromes - Hollway, G. E.; Suthers, Graeme K.; Haan, Eric A.; Thompson, Elizabeth; David, David J.; Gecz, Jozef; Mulley, John C. (Human genetics, 1997)
Five autosomal dominant craniosynostosis syndromes (Apert, Crouzon, Pfeiffer, Jackson-Weiss and Crouzon syndrome with acanthosis nigricans) result from mutations in FGFR genes. Fourteen unrelated patients with FGFR2-related craniosynostosis syndromes were screened for mutations in exons IIIa and IIIc of FGFR2. Eight of the nine mutations found have been reported, but one patient with Pfeiffer syndrome was found to have a novel G-to-C splice site mutation at-1 relative to the start of exon IIIc. Of those mutations previously reported, the mutation C1205G was unusual in that it was found in two related patients, one with clinical features of Pfeiffer syndrome and the other having mild Crouzon syndrome. This degree of phenotypic variability shows that the clinical features associated with a specific mutation do not necessarily breed true.